Interplay between Eimeria acervulina and Cryptosporidium parvum during In Vitro Infection of a Chicken Macrophage Cell Line (HD11) - Shahinaz Taha; Tran Nguyen-Ho-Bao; Lisa Maxi Berberich; Sandra Gawlowska; Arwid Daugschies; Zaida Rentería-Solís (Life, 2023)
Background: Eimeria acervulina is a frequent intestinal pathogen of chickens, causing economic impact on the poultry industry. Cryptosporidium parvum is a neglected parasite in chickens. However, because of its zoonotic potential, poultry cryptosporidiosis may pose a risk to public health. Little is known about the parasite–host interactions during coinfection with both parasites. In this study, we investigated the possible interactions during in vitro coinfection of E. acervulina and C. parvum in a chicken macrophage cell line (HD11). Methods: HD11 cells were inoculated with E. acervulina and C. parvum sporozoites and incubated 2, 6, 12, 24, and 48 h post infection (hpi). Mono-infections for each parasite were also investigated. Real-time PCR was used to quantify parasite replication. Additionally, macrophage mRNA expression levels of IFN-γ, TNF-α, iNOS, and IL-10 were measured. Results: For both parasites, multiplication was, in most groups, lower in the coinfection group (COIG) compared with mono-infections. However, at 6 hpi, the number of C. parvum copies was higher in co-infections. Intracellular replication started to decrease from 12 hpi onward, and it was almost undetectable by 48 hpi in all groups. Infections resulted in low expression of all cytokines, except at 48 hpi. Conclusions: Infection of avian macrophages with both E. acervulina and C. parvum seemed to hinder intracellular replication for both parasites in comparison to mono-infection. A clear reduction in intracellular parasites from 12 hpi onward details the important role potentially played by macrophages in host control of these parasites.